2017
DOI: 10.1186/s13104-017-2839-7
|View full text |Cite
|
Sign up to set email alerts
|

Item response theory analysis of the Utrecht Work Engagement Scale for Students (UWES-S) using a sample of Japanese university and college students majoring medical science, nursing, and natural science

Abstract: ObjectivesThe Utrecht Work Engagement Scale for Students has been used internationally to assess students’ academic engagement, but it has not been analyzed via item response theory. The purpose of this study was to conduct an item response theory analysis of the Japanese version of the Utrecht Work Engagement Scale for Students translated by authors. Using a two-parameter model and Samejima’s graded response model, difficulty and discrimination parameters were estimated after confirming the factor structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
1
6
0
3
Order By: Relevance
“…En el presente estudio, influenciado por trabajos relevantes De Bruin, Hil, Henn y Muller, 2013;Fongy Ho, 2015;Tsubakita, Shimazaki, Ito y Kawazoe, 2017;Vallières et al, 2017), se encontró una posible forma estructural alternativa para expresar mejor las relaciones entre los ítems y los factores del UWES. De acuerdo a los antecedentes sobre el UWES, este podría ser utilizado desde un enfoque de dos niveles de interpretación (multidimensional y unidimensional).…”
Section: Discussionunclassified
“…En el presente estudio, influenciado por trabajos relevantes De Bruin, Hil, Henn y Muller, 2013;Fongy Ho, 2015;Tsubakita, Shimazaki, Ito y Kawazoe, 2017;Vallières et al, 2017), se encontró una posible forma estructural alternativa para expresar mejor las relaciones entre los ítems y los factores del UWES. De acuerdo a los antecedentes sobre el UWES, este podría ser utilizado desde un enfoque de dos niveles de interpretación (multidimensional y unidimensional).…”
Section: Discussionunclassified
“…As the next step, the scale function of the UWES-17 was confirmed, and the five-point Likert-type scale was found to function appropriately. Tsubakita et al (2017) reported that a seven-point scale was excessively diverse for participants. Therefore, it did not function appropriately for the UWES-17.…”
Section: Discussionmentioning
confidence: 99%
“…However, this model has rarely been used to assess the UWES-17. Some studies utilized this model to examine the validity of the UWES-17 (De Bruin et al., 2013; Goliath-Yarde & Roodt, 2011; Tsubakita et al., 2017), but they did not have consistent and systematic standards for the validity tests. Therefore, the present study applied the Rasch model to examine the validity dimensions proposed by Messick (1995) to provide systematic and psychometric evidence regarding the validity of the UWES-17.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In assessing the judgemental validity, item 13 (“When studying, I am very resilient, mentally”) had the least median rating score and the main concern raised regarding the item was the difficulty in explaining the phrase “mentally resilience” in Sinhala language. The global literature suggests that modified versions of the UWES-S with removal of several items have been used in work engagement among high school, college, and university students [ 21 , 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%